Social Integration Processes of Immigrants in Schools of Huelva, Spain: Cultural Diversity and Educational Challenges - Karen García-Yepes (Universidad Politécnica Salesiana, 2017)
This article, focused on the social integration processes of immigrants in the school environment, derives as a result of a Master's Thesis developed in the city of Huelva (Spain). Its objective is to analyse the integration processes of immigrant children in the schools of Huelva, acknowledging the social role of schools regarding the children's formation and socialising opportunities. Methodology: discourse analysis applied to data gathered through in-depth interviews and workshops on interculturality with students, teachers and parents as participants. Main result of this analysis: the real challenge for the school is not to adapt curriculum's contents to the diversity of the environment, but to manage them effectively, meeting the particular needs of immigrants. It is there where citizens' rights and duties, as well as social participation opportunities are exercised. In this sense, it can be concluded that the challenge that schools face at intercultural contexts is to promote social integration through the development of abilities useful for life and for socialising. To this end, it is necessary to reorient the life course of children who left their roots, by promoting a dialog between their past and their present, which would allow the development of specific strategies contributing to the construction of their life course in a new social context.